FENOMENA BERBURU BABI STUDI TENTANG KEHARMONISAN DI NAGARI LIMO KAUM KAB. TANAH DATAR - Sari Purnama; Nofialdi Nofialdi; Deri Rizal (Institut Agama Islam Negeri Batusangkar, 2023)
The main problem in this thesis is the implementation and impact arising from hunting pigs on household harmony from the perspective of Islamic family law in Nagari Limo Kaum Kec. Lima Kab. Tanah Datar. The type of research used is field research with qualitative methods. The research results that the authors found were; First, the phenomenon of hunting pigs in Jorong Kubu is generally carried out twice a week. Initially, the purpose of hunting pigs was to eradicate pig pests that disturbed farmers' agricultural land and to become a sporting event. But at this time pig hunting is done because it's just a hobby. Second, negative impacts are caused such as reduced time for family gatherings, lack of attention to wife and children, starting to neglect obligations to his wife's children, insufficient family living needs, then frequent quarrels in the household. Third, the analysis of household harmony that hunts pigs in Jorong Kubu Rajo is the disruption of family functions to become a harmonious family.